1998
DOI: 10.1002/1529-0131(199809)41:9<1645::aid-art16>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene A4 hydrolase and leukotriene C4 synthase activities in human chondrocytes: Transcellular biosynthesis of leukotrienes during granulocyte-chondrocyte interaction

Abstract: Objective. To investigate the cooperation of chondrocytes and polymorphonuclear cells (PMN) in the biosynthesis of leukotrienes (LT).Methods. PMN, resting and interleukin-lastimulated cultured human chondrocytes, and mixtures of both cell types were incubated with A23187 and/or 14C-arachidonic acid (14C-AA). To explore the presence of LTC, synthase and LTA, hydrolase, the chondrocytes were incubated with authentic LTA,. Eicosanoids were analyzed using high performance liquid chromatography techniques.Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…The possible production of LTB 4 by chondrocytes is now under extensive examination, although previous studies have failed to identify 5-LO in these cells (12). LTs have been demonstrated to be potent factors in stimulating the synthesis of cytokines such as interleukin-1 (IL-1), IL-6, and IL-8 by synovial tissue (11).…”
supporting
confidence: 78%
“…The possible production of LTB 4 by chondrocytes is now under extensive examination, although previous studies have failed to identify 5-LO in these cells (12). LTs have been demonstrated to be potent factors in stimulating the synthesis of cytokines such as interleukin-1 (IL-1), IL-6, and IL-8 by synovial tissue (11).…”
supporting
confidence: 78%
“…This suggested that there was an important role for cell adhesion for transcellular biosynthesis to be efficient. Keratinocytes (Iversen et al, 1994) and chondrocytes (Amat et al, 1998) hydrolase and LTC 4 synthase. Alveolar macrophages were found to avidly take up exogenous LTA 4 and generate predominantly LTB 4 (Grimminger et al, 1991).…”
Section: E Additional Cell Interactionsmentioning
confidence: 99%
“…51, 2002 Leukotriene B 4 and guinea pig arthritis 547 consistent with these reports, because LY293111Na significantly inhibited the increase of MPO activity, a marker for tissue neutrophil content [30 -32], in the knee joint tissue at 24 h. These findings suggest that blockade of LTB 4 activity by LY293111Na seemed to lead to the decrease of PMN infiltration, and consequently ameliorated the cartilage and bone destruction induced by PMN-derived proteinases in guinea pig AIA [23]. In accordance with the present findings, Jovanovic et al recently examined the effect of ML-3000, a dual inhibitor of cyclooxygenase and 5-lipoxygenase, in dog OA model and concluded that LTB 4 has an important role in cartilage destruction [34], and another study revealed that chondrocytes cooperate with PMNs in the transcellular biosynthesis of LTB 4 [35].…”
Section: Discussionmentioning
confidence: 99%